2020
DOI: 10.1097/mcc.0000000000000691
|View full text |Cite
|
Sign up to set email alerts
|

Patient self-inflicted lung injury and positive end-expiratory pressure for safe spontaneous breathing

Abstract: Purpose of review The potential risks of spontaneous effort and their prevention during mechanical ventilation is an important concept for clinicians and patients. The effort-dependent lung injury has been termed ‘patient self-inflicted lung injury (P-SILI)’ in 2017. As one of the potential strategies to render spontaneous effort less injurious in severe acute respiratory distress syndrome (ARDS), the role of positive end-expiratory pressure (PEEP) is now discussed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 47 publications
0
99
0
18
Order By: Relevance
“…The level of specific stress-strain associated with the initiation of VALI P TP : transpulmonary pressure, V T : tidal volume, P: pressure, V: volume, F: force, A: area, L: length, RR: respiratory rate, VALI: ventilator-associated lung injury. and clinical studies have shown that excessively vigorous spontaneous efforts can lead to aggravation of VALI [28][29][30][31]. The risk of a condition coined as P-SILI or effort-induced lung injury is strongly associated with moderate-to-severe ARDS.…”
Section: Patient Self-inflicted Lung Injurymentioning
confidence: 99%
See 4 more Smart Citations
“…The level of specific stress-strain associated with the initiation of VALI P TP : transpulmonary pressure, V T : tidal volume, P: pressure, V: volume, F: force, A: area, L: length, RR: respiratory rate, VALI: ventilator-associated lung injury. and clinical studies have shown that excessively vigorous spontaneous efforts can lead to aggravation of VALI [28][29][30][31]. The risk of a condition coined as P-SILI or effort-induced lung injury is strongly associated with moderate-to-severe ARDS.…”
Section: Patient Self-inflicted Lung Injurymentioning
confidence: 99%
“…A too vigorous respiratory drive due to patient respiratory efforts and excessive P TP will result in global and local overdistension of lung tissue [30,33]. Thus, there are three primary mechanisms associated with P-SILI: pulmonary overdistension, increased lung blood flow, and patient ventilator asynchrony (double and reverse triggering) [31].…”
Section: Patient Self-inflicted Lung Injurymentioning
confidence: 99%
See 3 more Smart Citations